2022
DOI: 10.3390/s22207739
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Gas Distribution Asymmetry Effect on Coriolis Flowmeter Accuracy at Multiphase Metering

Abstract: Multiphase flows are encountered in various industries, and the Coriolis flowmeter (CFM) is considered a high potential flowmeter for the metering of these flows. However, the decoupling effect and asymmetrical gas distribution in a CFM might decrease the accuracy of its multiphase flow metering The asymmetry of gas distribution in a CFM and its influence on the metering accuracy have only been qualitatively investigated in a few studies. The present paper quantitatively describes the gas distribution asymmetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Enz [13] investigated the effect of asymmetric actuator and detector positions on the Coriolis flowmeter and measured phase shifts, and they found that both force and detector position asymmetries would lead to measurement errors. Shavrina et al [14] numerically studied the Coriolis flowmeter under various models with different gas volume fractions and flow conditions and verified it with experimental results. The study showed that the gas distribution asymmetry increased with increasing gas volume fraction and decreasing mixing flow rate and that the error of the Coriolis flowmeter was mainly caused by the asymmetry of the gas distribution.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Enz [13] investigated the effect of asymmetric actuator and detector positions on the Coriolis flowmeter and measured phase shifts, and they found that both force and detector position asymmetries would lead to measurement errors. Shavrina et al [14] numerically studied the Coriolis flowmeter under various models with different gas volume fractions and flow conditions and verified it with experimental results. The study showed that the gas distribution asymmetry increased with increasing gas volume fraction and decreasing mixing flow rate and that the error of the Coriolis flowmeter was mainly caused by the asymmetry of the gas distribution.…”
Section: Introductionmentioning
confidence: 90%
“…Based on the static pressure difference, the nozzle flowmeter has the ability to detect the flow rate [1]. At present, many researchers [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] have studied the internal flows and external characteristics of various types of flowmeters under different conditions from different aspects, and some researchers [21][22][23][24][25] have designed more suitable new flowmeters because of the limitations of the operating environment and the shortcomings of existing flowmeters.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement Principle for Mixture Density [6][7][8] Differential pressure across area reduction Gamma-ray attenuation [11] Coriolis (vibrating tubes): deformation Coriolis (vibrating tubes): natural frequency [12] Pipe strain (cross correlation): flow velocity Pipe strain (cross correlation): sound speed [13] Gas-liquid cyclonic separator, with a Coriolis meter in the liquid line and an orifice plate in the gas line…”
Section: Measurement Principle For Total Flow Ratementioning
confidence: 99%
“…The gamma-ray technique ( [6][7][8]) uses nuclear sources which have safety concerns and logistical hassles. A Coriolis meter may underperform at high gas fractions (above 20%), particularly with respect to measuring density, due to the phenomenon of gas-liquid decoupling [11]. Strain-sensor arrays may underperform at medium gas fractions (in the 20-80% range) due to a fundamentally weak relationship between the sound speed and fluid density [12].…”
Section: Measurement Principle For Total Flow Ratementioning
confidence: 99%
See 1 more Smart Citation